2018
DOI: 10.1186/s12891-018-2100-0
|View full text |Cite
|
Sign up to set email alerts
|

Does hallux valgus impair physical function?

Abstract: BackgroundThe relationships between radiographic hallux valgus (HV) and various physical functions independent of knee osteoarthritis (KOA) were examined among residents of a mountain village in Japan.MethodsStudy participants were recruited from mountain village residents aged ≥50 years. Participants’ height, weight, and body mass index (BMI) were measured, and baseline data, including age, sex, and foot pain, were obtained using interviews and questionnaires. Radiography of the feet and knees was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In this study, no signi cant between-group difference was found in the foot morphology, including for hallux valgus; even in the multiple logistic regression analysis, foot morphology was not among the signi cant factors. The prevalence of hallux valgus detected on radiographs in older Japanese men and women living in the community was 28.4% (3) and that in day care service users was > 50% (4). In this study, hallux valgus was found in about half of the older participants who needed some assistance with activities of daily living and are undergoing or had received ambulatory rehabilitation in a long-term care health facility.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In this study, no signi cant between-group difference was found in the foot morphology, including for hallux valgus; even in the multiple logistic regression analysis, foot morphology was not among the signi cant factors. The prevalence of hallux valgus detected on radiographs in older Japanese men and women living in the community was 28.4% (3) and that in day care service users was > 50% (4). In this study, hallux valgus was found in about half of the older participants who needed some assistance with activities of daily living and are undergoing or had received ambulatory rehabilitation in a long-term care health facility.…”
Section: Discussionmentioning
confidence: 52%
“…In a meta-analysis, the prevalence of hallux valgus in people aged ≥ 65 years was 35.7% (2). Hallux valgus was found in 28.4% of older Japanese people living in the community (3). Furthermore, more than 50% of 18 older adults who use day care services for assistance in daily life have hallux valgus (4).…”
Section: Introductionmentioning
confidence: 99%
“…HVA has been found to be inversely related to hallux loading and hallux plantarflexion strength. 26 This reduction in loading and flexion strength in hallux valgus results in increased pressure on the lesser MT, 20 which in turn can contribute to a hammertoe deformity. Because IMA has been found to increase in conjunction with HVA, 13 it is reasonable that the same association between hammertoe risk and HVA and IMA was found.…”
Section: Discussionmentioning
confidence: 99%
“…1,3) Because of hallux valgus and deformity of the lesser toes, toe flexor strength is often significantly reduced in older people. 6) Planar pres-sure during walking was found to be significantly lower in those with hallux valgus than in those without. 7) A reduction in the foot's contact area with the ground resulting from hallux deformity is considered to be the cause of reduced planar pressure.…”
Section: Introductionmentioning
confidence: 88%